Enhancing Healthcare Employee Performance Through Organizational Citizenship Behavior - Aulya Citra Safina; Alfato Yusnar Kharismasyah (Penerbit Goodwood, 2026)
Purpose: This study aimed to analyze the influence of authentic leadership and psychological contracts on employee performance satisfaction, with OCB as an intervening variable at PKU Muhammadiyah Purbalingga Hospital. Methodology/approach: This study applied a quantitative method with accidental sampling and included 136 participants. Data were obtained using a Likert scale questionnaire and processed using SmartPLS version 3.0. Results: Authentic leadership, psychological contracts, and OCB as mediating variables significantly influenced employee performance. Simultaneously, all the independent variables significantly influenced employee performance. Conclusions: Employee performance is enhanced through authentic leadership, the fulfillment of psychological contracts, and stronger Organizational Citizenship Behavior (OCB). This study recommends leadership development, fair and transparent contract management, and consistent recognition of OCB. Future research should be expanded to multiple institutions and include additional variables for broader generalization. Limitations: This study was conducted in only one hospital with similar respondents; therefore, the results may not be applicable to other settings. Furthermore, the study only collected data from a single point in time, so it cannot examine changes over time. Furthermore, data were collected via questionnaire, so respondents' answers may not fully reflect the actual situation. This study only examined authentic leadership, psychological contracts, and OCB; therefore, other factors that could influence employee performance were not addressed. Contributions: This study was limited to examining authentic leadership, psychological contracts, and OCB, while other possible determinants of employee performance were not explored. Additionally, since the research was conducted only at PKU Muhammadiyah General Hospital in Purbalingga, the scope of the study is constrained.